L’observation des pratiques d’enseignement : une approche à caractère sociologique - Yves Lenoir (Recherches en Éducation)
This article presents the sociological approach that characterizes processes of observing teaching practices as studied by the Canada Research Chair in Educative Intervention (CRCIE). The first part of the text defines what is here understood by observation. The second traces the research itinerary we have pursued, including components of successive research programs, in order to develop a conceptual frame of reference along with progressive foundations for this frame and the methodological procedures used to put it into practice. To conclude, the article summarizes the chief characteristics of the observation methodology in use before announcing new research orientations put into practice.